Mourning Headache: Revolution from Hegel to Kant and Back - Ivanova, Galina (Stasis, 2016)
Book review: Rebecca Comay, Mourning Sickness: Hegel and The French Revolution Stanford: Stanford University Press, 2011, xiv + 202pp., ISBN 978-0804761260 Artemy Magun, Negative Revolution: Modern Political Subject and its Fate After the Cold War New York: Bloomsbury, 2013, 288pp., ISBN 978-1441168085